Bibliometric analysis of the association between drinking water pollution and bladder cancer - Zhang, Ying; Liu, Mei; Wang, Jiajun; Han, Kexin; Han, Fuyu; Wang, Bicheng; Xie, Si; Yuan, Chunhui; Zhao, Mingdeng; Li, Shuo; Wang, Jun (Frontiers in Oncology, 2023)
Background: Bladder cancer has become an increasingly intractable health problem worldwide. Long-term drinking water pollution is known to promote its occurrence. This study aimed to analyze the research status, hot spots, and future trends of drinking water pollution and bladder cancer through extensive bibliometric examination to provide reference data for better prevention and management of bladder cancer. Methods: The Scopus database developed by Elsevier was browsed for articles that met the predefined criteria using the search terms related to drinking water and bladder cancer. Included articles were further evaluated by year of publication, subject category, institution, article type, source journal, authors, co-authorship networks, and text mining of titles by R software packages tm, ggplot2 and VOSviewer software. Results: In total, 687 articles were selected after a comprehensive literature search by the Scopus database, including 491 research articles , 98 review articles, 26 conference papers, 23 letters and 49 other documents. The total number of articles published showed an upward trend. The United States has the largest number of published articles (345 articles), institutions (7/10) and funding sponsors (top 5). The journal with the most publications was Environmental Health Perspectives, with 46 published. The highest number of citations up to 2330 times for a single article published in 2007 on the journal of Mutation Research. Professor Cantor K.P. was the highest number of publications with 35 articles and Smith A.H. was the most cited author with the number of citations reaching 6987 times overall and 225 times per article. The most frequent keywords excluding the search subject were “arsenic”, “chlorination”, “trihalomethane”, and “disease agents”. Conclusion: This study is the first systematic bibliometric study of the literature publications on drinking water pollution and BC. It offers an overall and intuitive understanding of this topic in the past few years, and points out a clear direction research hotspots and reveals the trends for further in-depth study in future.